Strategy for the introduction of alternative energy for the development of the circular economy of Ukraine - Stepaniuk, Olena; Huliaiev, Vitalii; Kovalenko, Alla; Anatskyi, Andrii; Filimonenko, Olha; Chubko, Larysa; Kuz, Tetiana (Problems of Environmental Biotechnology, 2024)
The strategy of alternative energy implementation for the development of the circular economy of Ukraine is considered